Debunkery : learn it, do it, and profit from it-- seeing through Wall Street's money-killing myths - Fisher, Kenneth L.; Hoffmans, Lara. (Hoboken, N.J. : John Wiley & Sons, 2011)
Money manager Ken Fisher highlights the most common money mistakes people make and reveals how to avoid them. In several short, accessible chapters, he discusses each myth/mistake, proves why it's actually costly or not a good idea, and then suggests a better strategy. The goal here is to go beyond simply telling you what to do, by giving you a strong understanding of the logic behind the advice and helping you more readily absorb it into your everyday thinking.--From publisher description.
A money manager outlines the most common and costly mistakes made in an effort to enhance financial well-being and discusses each mistake, proves why each is not a good idea, and offers better strategies.
'Fisher Investments Press.'
Keywords: Investments; Investments -- Decision making; Portfolio management; Investments